An Empirical Comparison of Coordinate Transformations from the Australian Geodetic Datum (AGD66 and AGD84) to the Geocentric Datum of Australia (GDA94) - Kinneen, Robert; Featherstone, Will (Spatial Sciences Institute, Australia, 2004)
This paper compares six coordinate transformation models and eight associated sets of (new and old) parameters over Australia. Test data comprising 161 Australian Geo-detic Datum 1966 (AGD66) and 327 Australian Geodetic Datum 1984 (AGD84) coor-dinates are transformed to the Geocentric Datum of Australia 1994 (GDA94) using these different models and parameters. The transformed coordinates are then com-pared with the, mainly satellite-derived, GDA94 coordinates of the same ground marks (i.e., control), then the results analysed and discussed. It must be stressed that this pa-per does not attempt to investigate or analyse the suitability of the mathematical models themselves, but makes an empirical comparison of past and existing approaches and parameters by using the same sample data sets. It is shown, as could be expected, that the more recent transformation parameters are the most suitable for coordinate trans-formations from the AGD to the GDA and vice versa.